2000
DOI: 10.1097/00001648-200003000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Air Concentrations of Nitrogen Dioxide and Sulfur Dioxide and Prevalence of Wheezing in School Children

Abstract: We report analysis of data on outdoor air pollution and respiratory symptoms in children collected in the Czech part of the international Small Area Variations in Air pollution and Health (SAVIAH) Project, a methodological study designed to test the use of geographical information systems (GIS) in studies of environmental exposures and health at small area level. We collected the following data in two districts of Prague: (1) individual data on 3,680 children (response rate 88%) by questionnaires; (2) census-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 49 publications
4
24
1
1
Order By: Relevance
“…In each study, exposure -effects relationships can be derived for the pollution range encountered in the study and thus, a wide pollution range is favorable. The eight districts of this study exhibited a wide range for each concerned pollutant, as shown clearly in Figure 5 where the ranges from major previous US /Europe studies are also shown for comparison purposes (Ware et al, 1986;Dockery et al, 1989Dockery et al, , 1996Spengler et al, 1996;Braun -Fahrlander et al, 1997;Peters et al, 1999b;Pikhart et al, 2000 ). The comparison indicates that the data on pollution levels collected in this study substantially extended the upper end of the pollution ranges of major published studies.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In each study, exposure -effects relationships can be derived for the pollution range encountered in the study and thus, a wide pollution range is favorable. The eight districts of this study exhibited a wide range for each concerned pollutant, as shown clearly in Figure 5 where the ranges from major previous US /Europe studies are also shown for comparison purposes (Ware et al, 1986;Dockery et al, 1989Dockery et al, , 1996Spengler et al, 1996;Braun -Fahrlander et al, 1997;Peters et al, 1999b;Pikhart et al, 2000 ). The comparison indicates that the data on pollution levels collected in this study substantially extended the upper end of the pollution ranges of major published studies.…”
Section: Discussionsupporting
confidence: 68%
“…Health effects of exposure to ambient air pollution have been extensively investigated in epidemiological studies in North American and European cities ( Chapman et al, 1985;Ware et al, 1986;Dockery et al, 1993Dockery et al, , 1996Pope et al, 1995;Peters et al, 1999a,b;Pikhart et al, 2000 ). Although these studies have found, more or less, evidence of adverse health effects of air pollution exposure, the available results remain subject to significant uncertainties in several key areas including: (1 ) the community health effects of longterm exposure; ( 2) the relative health importance of different air pollutants and different size fractions and constituents of atmospheric particles; (3 ) the ethnic, demographic, and other factors that influence susceptibility to air pollution effects.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to initial expectations, the research indicated no significant differences in the average values of the PF tests across the townships, despite their distinctively different air pollution levels and the wealth of evidence accumulated to date on the link between air pollution and PF development in children (see inter alia Peters et al, 1999a, b;Pikhart et al, 2000;Gauderman et al, 2000Gauderman et al, , 2004Schwartz, 2004).…”
Section: Hadera Region Israel As a Case Studycontrasting
confidence: 64%
“…In these conditions, the current address cannot be representative of the whole life living places. All of the teams who have used such dispersion models, with the exception of Pikhart et al (2000), only estimated outdoor concentrations at home without considering the exposure in front of work places or day-care centers, and therefore run the risk of misclassification. Our approach highlights significant disparities in time-weighted NO x levels in front of the children's living places, whereas the use of urban background pollution data provided by the air quality networks would not have described such diversity.…”
Section: Exposure To Traffic Air Pollutantsmentioning
confidence: 99%
“…Only four teams Pikhart et al, 2000;Hoek et al, 2001;Brauer et al, 2002;Gehring et al, 2002;Hoek et al, 2002;Brauer et al, 2003) had recourse to statistical regression models to estimate exposure to traffic air pollutants (TAP). Moreover, pollutant dispersion models have been developed to improve the estimate of exposure levels (Hertel and Berkowicz, 1989;Benson, 1992;Eerhens et al, 1993;Berkowicz et al, 1994), but they have rarely been used in epidemiology (Larssen et al, 1993;Pershagen et al, 1995;Bartonova et al, 1999;Clench-Aas et al, 1999a, b;Briggs et al, 2000;Clench-Aas et al, 2000;Nyberg et al, 2000;Pikhart et al, 2000;Raaschou-Nielsen et al, 2000;Bellander et al, 2001;Raaschou-Nielsen et al, 2001;Zmirou et al, 2002).…”
Section: Introductionmentioning
confidence: 99%